The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Proceedings of the 15th International Workshop on Content-Based Multimedia Indexing 2017
DOI: 10.1145/3095713.3095719
|View full text |Cite
|
Sign up to set email alerts
|

The 3D-Pitoti Dataset

Abstract: Abstract-The development of powerful 3D scanning hardware and reconstruction algorithms has strongly promoted the generation of 3D surface reconstructions in different domains. An area of special interest for such 3D reconstructions is the cultural heritage domain, where surface reconstructions are generated to digitally preserve historical artifacts. While reconstruction quality nowadays is sufficient in many cases, the robust analysis (e.g. segmentation, matching, and classification) of reconstructed 3D data… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
(37 reference statements)
0
9
0
Order By: Relevance
“…Using AI to analyse rock art is a newly emerging field in both data science and archaeology. In the course of the ERC funded 3D-Pitoti project, several methods have been proposed and tested on a relatively limited set of rock art images (Poier et al, 2016(Poier et al, , 2017Zeppelzauer et al, 2016;. 2D and 3D documentations were used to create an automatic segmentation algorithm.…”
Section: Previous Work and Research Questionmentioning
confidence: 99%
“…Using AI to analyse rock art is a newly emerging field in both data science and archaeology. In the course of the ERC funded 3D-Pitoti project, several methods have been proposed and tested on a relatively limited set of rock art images (Poier et al, 2016(Poier et al, , 2017Zeppelzauer et al, 2016;. 2D and 3D documentations were used to create an automatic segmentation algorithm.…”
Section: Previous Work and Research Questionmentioning
confidence: 99%
“…Petroglyph, in other words rock-art, analysis [8,28,[31][32][33]46] is another related topic to our glyph recognition task. For petroglyph segmentation that can be considered as foreground/background classification of pixels, Seidl et al [31] studied various combinations of traditional textural features.…”
Section: Related Workmentioning
confidence: 99%
“…Specifically, third order Gray-Level Co-occurrence Matrix (GLCM) and Local Binary Patterns (LBP) were shown to outperform color or dense-SIFT features in a late classification fusion setting [31]. In a recent 3D petroglyph segmentation study, Poier et al [28] reported that fully-connected CNNs produced better segmentation results thanks to capturing the spatial context better than random forests. Poier et al [28] also noted that the contribution of traditional color and textural features to final segmentation maps was negligible, therefore only depth maps and orthophotos generated from the point clouds were used as input to the classifiers.…”
Section: Related Workmentioning
confidence: 99%
“…SfM is well-suited for identifying petroglyphs on uneven surfaces, such as those often found in caves (Caninas et al 2016; Fritz et al 2016), and SfM models give spatial context to petroglyphs that is helpful for interpretation (Alexander et al 2015; Janik et al 2007). Because of the value of SfM for the interpretation of rock art, archaeologists have recently explored methods of digitally enhancing model visualization (e.g., Carrero-Pazos et al 2016; Vilas-Estevez et al 2016), have developed specialized tools for efficiently collecting rock art photographs (e.g., Höll et al 2014), and have segmented rock art models to effectively store and query models in databases (e.g., Poier et al 2016; Zeppelzauer et al 2015; Zeppelzauer et al 2016). Significantly, SfM mapping has a substantially lower impact on rock art than tracing, and monitoring of archaeological features through SfM mapping can be used to identify conservation priorities (Plets et al 2012).…”
Section: Photogrammetry and Structure From Motion (Sfm)mentioning
confidence: 99%